Cerebrovascular Complications in Bacterial Meningitis - Shahrzad S. Deliran; Matthijs C. Brouwer; Diederik van de Beek (Stroke: Vascular and Interventional Neurology)
The objective is to describe a comprehensive analysis of patients with bacterial meningitis exacerbate by cerebrovascular complications. We reviewed the literature on cerebrovascular complications in adult patients with bacterial meningitis. Cerebrovascular complications occur in one fourth of patients with bacterial meningitis. The most common cerebrovascular disease complicating bacterial meningitis are cerebral infarctions (9%–25%), intracerebral hemorrhage (1%–7%), cerebral venous thrombosis (1%–10%), and subarachnoid hemorrhage (1%–5%). Streptococcus pneumoniae and Staphylococcus aureus are the primary causative pathogens leading to these complications. The pathophysiological mechanisms have not completely been elucidated but involve vasculitis, endothelial dysfunction, hypercoagulability, aggregation, and complement activation. Cerebrovascular complications are important predictors of unfavorable outcome and death, and the use of adjunctive dexamethasone has been described to reduce the incidence. In conclusion, cerebrovascular complications are common in bacterial meningitis and are strongly associated with unfavorable outcomes and death. Although our understanding of the pathophysiology is evolving, there remains a need for novel treatment strategies to address these complications.